Enhanced Expression of CD47 Is Associated With Off-Target Resistance to Tyrosine Kinase Inhibitor Gefitinib in NSCLC - Nigro, Annunziata; Ricciardi, Luca; Salvato, Ilaria; Sabbatino, Francesco; Vitale, Monica; Crescenzi, Maria Assunta; Montico, Barbara; Triggiani, Massimo; Pepe, Stefano; Stellato, Cristiana; Casolaro, Vincenzo; Dal Col, Jessica (Frontiers in Immunology, 2020)
Mutual interactions between cancer cells and the tumor microenvironment importantly contribute to the development of tyrosin kinase inhibitor (TKI) resistance in patients affected by EGFR-mutant NSCLC. In particular, immune recognition-associated proteins with impact on tumor cell clearance through phagocytosis, such as CD47 and calreticulin, could contribute to adaptive resistance and immune-escape. Preclinical studies targeting the anti-phagocytic CD47 molecule showed promising results in different cancer types including lung cancer, but no data are available on its role in patients acquiring resistance to EGFR TKI treatment. We analyzed the functional contribution of CD47 and calreticulin to immune surveillance and evasion in a panel of NSCLC cell lines carrying sensitizing or resistant mutations in the EGFR gene, following treatment with the TKI gefitinib and after in vitro development of gefitinib resistance. While CD47 and calreticulin protein levels were markedly variable in both EGFR-mutant and wild-type cell lines, analysis of NSCLC transcriptomic dataset revealed selective overexpression of CD47 in patients carrying EGFR mutations. EGFR inhibition significantly reduced CD47 expression on the surface of pre-apoptotic cells, favoring more efficient engulfment of cancer cells by monocyte-derived dendritic cells. This was not necessarily associated with augmented surface exposure of calreticulin or other molecular markers of immunogenic cell death. Moreover, CD47 expression resulted up-regulated following in vitro drug resistance development, and blocking of this protein by a specific monoclonal antibody increased the clearance of EGFR-TKI resistant cells by phagocytes. Our study supports CD47 neutralization by specific monoclonal antibody as a promising immunotherapeutic option for naïve and resistant EGFR-mutant NSCLCs.